The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/v13010082
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Respiratory Tissue and Cell Line Models to Examine Glycosylation Machinery during SARS-CoV-2 Infection

Abstract: Glycosylation, being the most abundant post-translational modification, plays a profound role affecting expression, localization and function of proteins and macromolecules in immune response to infection. Presented are the findings of a transcriptomic analysis performed using high-throughput functional genomics data from public repository to examine the altered transcription of the human glycosylation machinery in response to SARS-CoV-2 stimulus and infection. In addition to the conventional in silico functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…Detecting changes in gene expression in relevant tissues during SARS-CoV-2 infection through various functional genomic methods (e.g., microarrays and RNA-sequencing-based transcriptomics) can increase understanding of molecular mechanisms involved in COVID-19, plus host-pathogen interactions (8)(9)(10). Transcriptomic studies in COVID-19 patients used lung epithelial cells, nasopharyngeal swabs, bronchoalveolar lavage fluid (9,(11)(12)(13)(14), or peripheral blood mononuclear cells (PBMCs) (6,8,15). However, differential gene expression analysis focuses more on individual effects of genes (16), whereas genes interact in complex biological gene networks (17).…”
Section: Introductionmentioning
confidence: 99%
“…Detecting changes in gene expression in relevant tissues during SARS-CoV-2 infection through various functional genomic methods (e.g., microarrays and RNA-sequencing-based transcriptomics) can increase understanding of molecular mechanisms involved in COVID-19, plus host-pathogen interactions (8)(9)(10). Transcriptomic studies in COVID-19 patients used lung epithelial cells, nasopharyngeal swabs, bronchoalveolar lavage fluid (9,(11)(12)(13)(14), or peripheral blood mononuclear cells (PBMCs) (6,8,15). However, differential gene expression analysis focuses more on individual effects of genes (16), whereas genes interact in complex biological gene networks (17).…”
Section: Introductionmentioning
confidence: 99%
“…Complementary structural and mass spectrometry analyses of the SARS-CoV-2 S protein confirmed that, like the related proteins from SARS-CoV and MERS-CoV viruses, the SARS-CoV-2 S protein is also extensively glycosylated. , Glycosylation has a myriad of roles in viral pathobiology including shielding vulnerable neutralizing epitopes, shaping viral tropism, and mediating S protein folding and stability. Figure A shows that there are 22, 22, and 23 glycosylation sites in the SARS-CoV-2, SARS-CoV, and MERS-CoV S proteins, respectively, with glycosylation preferentially localizing to the NTD, S1/S2 boundary, and stem helix of the S2 fusion domain. , Using the first reported structure of the SARS-CoV-2 spike protein (6VSB), Grant et al generated 3D structures of the S protein glycoforms and subjected them to molecular dynamic (MD) simulations to determine the antibody-accessible surface area . Despite only accounting for 17% of the molecular weight of the S trimer, Grant et al found that the glycans shield approximately 40% of the S protein surface (Figure B).…”
Section: Entry Into the Cellmentioning
confidence: 91%
“… 94 , 95 Glycosylation has a myriad of roles in viral pathobiology including shielding vulnerable neutralizing epitopes, shaping viral tropism, and mediating S protein folding and stability. 94 100 Figure 10 A shows that there are 22, 22, and 23 glycosylation sites in the SARS-CoV-2, SARS-CoV, and MERS-CoV S proteins, respectively, with glycosylation preferentially localizing to the NTD, S1/S2 boundary, and stem helix of the S2 fusion domain. 94 , 95 Using the first reported structure of the SARS-CoV-2 spike protein ( 6VSB ), Grant et al generated 3D structures of the S protein glycoforms and subjected them to molecular dynamic (MD) simulations to determine the antibody-accessible surface area.…”
Section: Entry Into the Cellmentioning
confidence: 99%
“…The Spike protein and, more specifically, its receptor-binding domain (RBD) on the virus surface are responsible for binding to human angiotensin-converting enzyme 2 (hACE2) on the host cell. Hence, because of their central role in viral entry, the Spike and the RBD are established immunogens in SARS-CoV-2 vaccines ( 2 , 3 ). mRNA-based and viral-vectored vaccines encoding the Spike protein have gained regulatory approvals and are being massively deployed presently.…”
Section: Introductionmentioning
confidence: 99%